Manufacturing polymer/metal macro-composite structure for vibration damping - Altan, Mihrigul; Bayraktar, Meral; Yavuz, Burak (SPRINGER LONDON LTD, 2016)
Metal/polymer-combined macro-composite structures are representative of a unique combination to achieve improved quality of products. In this work, a non-traditional method for manufacturing metal/polymer-combined sandwich structure for vibration damping was generated from a traditional method, plastic injection molding, which is then called plastic injection forming (PIF). In the experimental study, aluminum plates with dimensions for the metal part of the macro-composite and three different types of polymeric material were used for the core of the sandwich structure: polypropylene, nano-titan dioxide-added polypropylene, and thermoplastic elastomer (TPE). For determining flexural strength of macro-composite structures, a 3-point bending test was applied. Finite element analysis by commercial ANSYS code was utilized to compare the bending results with finite element method (FEM). Force transmissibility test was performed in order to define damping characteristics of the macro-composite structures. The damping ratio of each structure was figured out by performing frequency analysis. Finally, damping characteristics of these composite structures were discussed by comparing their damping ratios.
Keywords: Polymer/metal sandwiches; Macro-composite; Plastic injection molding; Vibration damping; SANDWICH STRUCTURES; FIBER-COMPOSITE; DIRECT-ADHESION; HONEYCOMB; Automation & Control Systems; Engineering